2019
DOI: 10.14444/6038
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Diagnosis of Tandem Spinal Stenosis: A Retrospective Institutional Review

Abstract: Background: Tandem spinal stenosis (TSS) is defined as simultaneous spinal stenosis in the cervical, thoracic, and/or lumbar regions and may present with both upper and lower motor neuron symptoms, neurogenic claudication, and gait disturbance. Current literature has focused mainly on the prevalence of TSS and treatment methods, while the incidence of delayed TSS diagnosis is not well defined. The purpose of this study was to determine the incidence of delayed TSS diagnosis at our institution and describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
10
0
3
Order By: Relevance
“…For other authors, the operative order was dictated by the importance of the symptoms. They started with the most symptomatic spinal region [3,11,15]. In his study, Luo [16] noted a faster decompensation of cervical signs in patients previously operated on at the lumbar level, which he did not find in patients whose procedure was reversed.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…For other authors, the operative order was dictated by the importance of the symptoms. They started with the most symptomatic spinal region [3,11,15]. In his study, Luo [16] noted a faster decompensation of cervical signs in patients previously operated on at the lumbar level, which he did not find in patients whose procedure was reversed.…”
Section: Discussionmentioning
confidence: 95%
“…This opinion is shared by Krishnan [17]. The postoperative evolution, satisfactory in a large number of studies, had not shown a significant difference whatever the mode or order of the surgical gestures [9,11,12,15]. The determining elements of this evolution would be the duration of evolution of the signs and the speed of the realization of the surgical act according to Zulkefli [15].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations